GENDER CONFLICTS OF STUDENTS - Moskalyk, H. F.; Bulach, M. O. (Anthropological Measurements of Philosophical Research, 2017)
Actuality of work. Student age has the most favourable conditions for psychological, biological and social development; however, there are reasons why such natural advantages over other social groups can be completely or partially levelled. One of them is the presence of conflicts in the life of a student, a special group, among which there are women. The causes of the emergence of gender conflicts in individual social groups and the strategies for their solution have not been sufficiently explored and require further study and, therefore, are relevant. Purpose of the article is to investigate the causes of gender conflicts among students as a separate social group and to develop measures to address them and prevent them. Methodology. The research conducted in the work is based on the analysis and generalization of the causes of the emergence of gender conflicts among students, the identification of the main sources of information that form the consciousness of children and adolescents, and also influence their attitude to gender equality. Originality. The nature of gender conflicts has been quite effectively studied for a long time. However, the scope of research is limited to the most numerous social groups, such as the family, labour collective, political and public organizations, etc. Being a dynamic and socio-demographic formation, the students perform an important function in society – it takes a direct part in the transformation of all spheres of the life activity of the society. Based on the study of the objective conditions of the social environment with certain models of socialization that form the consciousness of students from early childhood, a three-component system of influence was first proposed, which is aimed at overcoming gender inequality and preventing gender conflicts among students. At the same time, the interaction of the components of the system will allow to minimize the gender inequality index in our country. Conclusions. Based on the conducted research, the authors came to the conclusion that any part of their life activity can become the sphere of occurrence of gender conflicts of students: from the choice of the direction of vocational training and the educational process to the arrangement of living conditions. The main cause of gender conflicts among students is gender inequality, which is formed in their minds. While in our society there are gender stereotypes that influence the formation of the consciousness of people from childhood and are promoted by all available sources of information, such a phenomenon as gender inequality cannot be considered overcome.